A Laboratory Test Expert System for Clinical Diagnosis Support in Primary Health Care - Rodrigo Fernandez-Millan; Jose-Amelio Medina-Merodio; Roberto Barchino Plata; Jose-Javier Martinez-Herraiz; Jose-Maria Gutierrez-Martinez (Applied Sciences, 2015)
Clinical Decision Support Systems have the potential to reduce lack of communication and errors in diagnostic steps in primary health care. Literature reports have showed great advances in clinical decision support systems in the recent years, which have proven its usefulness in improving the quality of care. However, most of these systems are focused on specific areas of diseases. In this way, we propose a rule-based expert system, which supports clinicians in primary health care, providing a list of possible diseases regarding patient’s laboratory tests results in order to assist previous diagnosis. Our system also allows storing and retrieving patient’s data and the history of patient’s analyses, establishing a basis for coordination between the various health care levels. A validation step and speed performance tests were made to check the quality of the system. We conclude that our system could improve clinician accuracy and speed, resulting in more efficiency and better quality of service. Finally, we propose some recommendations for further research.